Multifunctionality and path dependence: Farmer decision-making in the peri-urban fringe. (December 2022) - Song, Bingjie; Robinson, Guy M.; Bardsley, Douglas K.
Abstract: Peri-urban areas provide both challenges and opportunities for agricultural production, often generating complex multifunctional landscapes and high levels of farm diversification. In Australia, this complexity reflects the interplay of factors affecting farmer decision-making against a backdrop of limited government support for farmers and some of the world's most extensive urban sprawl. Drawing on data from a sample of farms in South Australia's Adelaide Hills, part of the peri-urban fringe of the state capital, Adelaide, this analysis uses the concept of farm business trajectories and path dependence to investigate how different types of farmers are shaping multifunctionality. Using a sequential mixed methods approach that combines a questionnaire survey and in-depth interviews, the research investigates alternative farming pathways and conceptualises both negative and positive aspects of path dependency. Applying a two-step cluster analysis, seven different groups of farmers are recognised in terms of recent and intended changes to their farming system. A clear distinction is drawn between commercial, productivist enterprises and the semi- or non-commercial smallholdings that are contributing to growing landscape fragmentation. The growth of farm-based tourism and processing, alternative food networks, and amenity lifestyles are portrayed as part of a spectrum of farm pathways nested within the multifunctional peri-urban landscape. Some 'lock in' mechanisms are supporting adaptation to changing socio-economic and land use conditions, while others are hindering opportunities for sustainable outcomes, but together the complexity of multifunctional agriculture is adding to regional resilience. Highlights: Multifunctional agriculture (MFA) comprises diverse farm-based enterprises. Path dependence, inertia and lock-in contribute to varied farming trajectories. Within MFA productivist trajectories contrast with less commercial alternatives. Distinctive farm clusters contribute differentially to MFA implying diverse futures. MFA in the peri-urban fringe involves deagrarianisation and landscape fragmentation.